2012
DOI: 10.1017/s0022215112001338
|View full text |Cite
|
Sign up to set email alerts
|

Management of recurrent acute otitis media in children: systematic review of the effect of different interventions on otitis media recurrence, recurrence frequency and total recurrence time

Abstract: Prophylactic antibiotics are effective in reducing otitis media recurrence, recurrence frequency and total recurrence time. Tympanostomy tube insertion failed to reduce the prevalence of otitis media recurrence, but reduced the recurrence frequency and total recurrence time. Adenoidectomy reduced otitis media recurrence; results on otitis media recurrence frequency differed but on average there was a reduction; however, the two studies with relevant data on total recurrence time had contradictory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…[20] However, this study did not provide a definition of recurrent URIs, recurrent otitis, or recurrent pneumonia, making it difficult to compare the reported prevalence with the population-level prevalence, particularly when as many as 46% of children in the general population have three or more episodes of otitis media by three years of age. [21] In another study, the prevalence of recurrent URI (defined as 3 episodes per year for 3 successive years) and recurrent UTI (defined as 3 episodes over a 2 year period) was 42% and 9%, respectively, [14] One study of SIgAD patients found that 57.84% had atopic dermatitis, although only 10.17% of those had elevated IgE. [28] These studies are generally small, yielding significant variability between resulting prevalence estimates.…”
Section: Complicationsmentioning
confidence: 99%
“…[20] However, this study did not provide a definition of recurrent URIs, recurrent otitis, or recurrent pneumonia, making it difficult to compare the reported prevalence with the population-level prevalence, particularly when as many as 46% of children in the general population have three or more episodes of otitis media by three years of age. [21] In another study, the prevalence of recurrent URI (defined as 3 episodes per year for 3 successive years) and recurrent UTI (defined as 3 episodes over a 2 year period) was 42% and 9%, respectively, [14] One study of SIgAD patients found that 57.84% had atopic dermatitis, although only 10.17% of those had elevated IgE. [28] These studies are generally small, yielding significant variability between resulting prevalence estimates.…”
Section: Complicationsmentioning
confidence: 99%
“…Children aged less than six months are considered high risk because recurring bouts of otitis media may predispose them to complications that include speech difficulties and hearing loss. 1,2 In our study, we reported the highest incidences of non-resolving acute otitis media following initial paracetamol usage in children aged 7-12 months (43.5 per cent) and 2-5 years (42.1 per cent). 3 In chronic suppurative otitis media (CSOM) where microbial aetiology is implicated, it is important that antibiotics be given.…”
Section: Authors' Replymentioning
confidence: 54%
“…10,11 Review study by Cheong et al which compares the effects of interventions by prophylactic antibiotics, tympanostomy tube insertion and adenoidectomy concluded that prophylactic antibiotics are effective in reducing otitis media recurrence, recurrence frequency and total recurrence time. 12 There are several studies where a single antibiotic versus placebo control or comparison between antibiotics like amoxicillin, septran, macrolides etc. have been made with a result that prophylactic antibiotics are effective in the management of recurrent AOM.…”
Section: Discussionmentioning
confidence: 99%